A Quality Improvement Initiative to Enhance the Treatment of Children With Severe Acute Malnutrition in Nepal. (14th June 2022) - Shrestha, Manisha; Chapagain, Binod; Pandey, Pooja; Mandal, Raj; Perry, Kelly; Pun, Bhim; Weissman, Amy
Abstract: Objectives: Despite being implemented for decades, Nepal's Integrated Management of Acute Malnutrition program has experienced several implementation challenges such as low coverage, stock outs of ready-to-use therapeutic food supplies, poor reporting, loss to follow up and sub-optimal counselling. To address these and build a culture of continuous service delivery improvement, the Suaahara-II program adopted and assessed a quality improvement (QI) approach. Methods: Change ideas, including increasing case identification through various platforms, developing QA standards to measure service quality, and providing incentives for female community health volunteers, were implemented as part of the QI initiative in four pilot municipalities. To assess changes in outcomes such as cure rate and number of cases identified and lost to follow-up, baseline information was collected over six months pre-implementation and performance was monitored throughout the QI implementation cycle of 17 months (February 2019—June 2021). We also analyzed secondary data from the government health management information system and established a monitoring mechanism to ensure data quality for outcome measures. For the outcome measure of service quality score, we developed a quality assurance (QA) checklist to score services while treating children with severe acute malnutrition (SAM). Results: Our findings suggest that the QI effort was effective. The SAM cure rate increased from 67.4% pre-implementation to 80% post-implementation and the loss-to-follow-up rate declined from 26% to 8%. The number of new SAM cases fluctuated between 0–20 cases per month likely due to restrictions to mobility caused by the COVID-19 pandemic. Although there is no comparison to facilities that did not participate in the QI pilot, those that did had an average quality assurance score of 82.4%–above the 80% benchmark. Conclusions: We found that the QI approach helped improve SAM cure rate, limited loss-to-follow-up and improved quality of case management for children with SAM. To successfully and sustainably implement QI to improve service delivery, leadership and local government accountability, regular coaching support and collaborative team efforts are key. Funding Sources: United States Agency for International Development (USAID).